(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The Constitution of India under Article 39-A mandates for free legal aid to the poor and weakersections of society. The concept of legal aid was originally introduced in India in 1952 when the Indiangovernment began to address the subject of legal assistance for the poor in many Law Ministers and LawCommissions conferences. In 1960, the government set guidelines for legal assistance programmes. Atpresent Legal Aid is the provision of free legal assistance to the poor and needy who cannot afford toengage a lawyer to represent them in a court, tribunal, or before a government body. Legal Aid is atechnique of ensuring that no one is denied justice for whatever reason. And free legal aid undoubtedlyis beneficial to poor people and has been instituted with the noble purpose. Yet it has become a goodground for breeding corruption. Free legal aid for a fee is common practice. This paper discusses theconstitutional provisions for free legal aid in India.